Metformin Effects on SHIP2, AMPKs and Gut Microbiota: Recent Updates on Pharmacology - Shivaprakash, Priyanka; Beeraka, Narasimha Murthy; Madhunapantula, Subba Rao V.; Nikolenko, Vladimir N.; Basalingappa, Kanthesh M. (Current Medicinal Chemistry, 2025)
IntroductionMetformin, a biguanide on the WHO’s list of essential medicines has a long history of 50 years or more in treating hyperglycemia, and its therapeutic saga continues beyond diabetes treatment. Glucoregulatory actions are central to the physiological effects of metformin; surprisingly, the precise mechanism with which metformin regulates glucose metabolism is not thoroughly understood yet.MethodsThe main aim of this review is to explore the recent implications of metformin in hepatic gluconeogenesis, AMPKs, and SHIP2 and subsequently to elucidate the metformin action across intestine and gut microbiota. We have searched PubMed, Google scholar, Medline, eMedicine, National Library of Medicine (NLM), clinicaltrials.gov (registry), and ReleMed for the implications of metformin with its updated role in AMPKs, SHIP2, and hepatic gluoconeogenesis, and gut microbiota. In this review, we have described the efficacy of metformin as a drug repurposing strategy in modulating the role of AMPKs lysosomal-AMPKs, and also, the controversies associated with metformin.ResultsResearch suggests that biguanide exhibits hormetic effects depending on the concentrations used (micromolar to millimolar). The primary mechanism attributed to metformin action is the inhibition of mitochondrial complex I, and subsequent reduction of cellular energy state, as observed with increased AMP or ADP ratio, thereby metformin can also activate the cellular energy sensor AMPK to inhibit hepatic gluconeogenesis. However, new mechanistic models have been proposed lately to explain the pleiotropic actions of metformin; at low dose, metformin can activate lysosomal-AMPK via the AXIN-LKB1 pathway. Conversely, in an AMPK-independent mechanism, metformin-induced elevation of AMP suppresses adenylate cyclase and glucagon-activated cAMP production to inhibit hepatic glucose output by glucagon. Metformin inhibits mitochondrial glycerophosphate dehydrogenase; mGPDH, and increases the cytosolic NADH/NAD+, affecting the availability of lactate and glycerol for gluconeogenesis. Metformin can inhibit Src homology 2 domain-containing inositol 5-phosphatase 2; SHIP2 to increase the insulin sensitivity and glucose uptake by peripheral tissues. In addition, new exciting mechanisms suggest the role of metformin in promoting beneficial gut microbiome and gut health. Metformin regulates duodenal AMPK activation, incretin harmone secretion and bile acid homeostasis to improve intestinal glucose absorption and utilization.ConclusionThe proper understanding of the key regulators of metformin actions is of utmost importance to enhance its pleotropic benefits on diabetes and beyond.
Keywords: AMPK